Overview of the French and European Regulations on Aerial Drones (Tema Central) - Baudouin, Laurène (2021)
Since July 2018, the European Union member states have had appropriate regulations governing the manufacture and use of all types of civil drones. Although, most of these states already had national laws governing the use of drones. These are still in force for military and state drones. However, other legal and ethical issues still deserve attention. Prominently, drones raise several issues regarding the protection of privacy and the use of personal data. Indeed, drones used by civilians may be equipped of different types of sensors that can collect a large amount of data. Consequently, the use of drones by companies or amateurs could increase the surveillance effect and even affect the behaviour of individuals. Also, in the context of the increasing use of drones by law enforcement agencies, issues arise regarding the limits applied to fundamental rights. Beyond the simple use of camera-equipped drones, it is the various fundamental rights they reach that are of most concern. The use of aerial drones for surveillance purposes is the most representative case in this regard. In order to avoid abuses, some States are working to develop regulations to govern the use of drones by law enforcement and rescue services.